Luxe, genre et émotions dans l’hôtellerie - Gabriele Pinna (La Nouvelle Revue du Travail)
The social distance between employees and customers in the luxury hotel industry forces the former to display enthusiasm and spontaneity even as they are supposed to recognise the latter’s symbolic capital and social superiority. It is a field where the rules governing feelings are gendered and built around a sexual division of labour. Women are supposed to be more empathetic and sensitive yet responsive to male customers and colleagues’ attempts at seduction and sexual behaviour. Men perform tasks specific to the world of luxury that have high symbolic value and imply great self-control – but they are also likely to be complicit with some customers’ efforts at seduction and gallantry. Employees could theoretically distance themselves from these emotional constraints, notably by reversing today’s symbolic social and emotional order by laughing at customers and mocking them. Having said that, they often leave the luxury hotel industry after a few years due to the suffering they have experienced, a symptom of the problems they face in managing the rules governing feelings.